2004
DOI: 10.1038/sj.onc.1208139
|View full text |Cite
|
Sign up to set email alerts
|

HES-1 inhibits 17β-estradiol and heregulin-β1-mediated upregulation of E2F-1

Abstract: We have previously shown that expression of the transcription factor HES-1 is required for the growthinhibitory effect of all-trans retinoic acid on MCF-7 cells. In this study, we have used T47D cells with tetracyclinregulated expression of wild-type or a dominant-negative form of HES-1. Expression of HES-1 in T47D cells inhibited G 1 /S-phase transition and activation of Cdk2 elicited by estrogen. Estrogen treatment of T47D cells caused increased expression of E2F-1, and this expression was inhibited by cotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 32 publications
(48 reference statements)
2
49
0
Order By: Relevance
“…Sustained Hes1 expression leads to G1 phase retardation of the cell cycle (Yoshiura et al, 2007). Hes1 can directly or indirectly repress the transcription of cell cycle-related genes, including E2f1, p21Cip1, p27Kip1, and p57Kip2 (Castella, et al, 2000;Georgia, et al, 2006;Hartman et al, 2004;Murata et al, 2005). Hes1 oscillation may be important for efficient cell proliferation.…”
Section: Hes1 Oscillation and Cell Proliferation In Cultured Cellsmentioning
confidence: 99%
“…Sustained Hes1 expression leads to G1 phase retardation of the cell cycle (Yoshiura et al, 2007). Hes1 can directly or indirectly repress the transcription of cell cycle-related genes, including E2f1, p21Cip1, p27Kip1, and p57Kip2 (Castella, et al, 2000;Georgia, et al, 2006;Hartman et al, 2004;Murata et al, 2005). Hes1 oscillation may be important for efficient cell proliferation.…”
Section: Hes1 Oscillation and Cell Proliferation In Cultured Cellsmentioning
confidence: 99%
“…This upregulation is important for the antiestrogenic effect of atRA (Muller et al 2002) and appears to affect the expression of the cell cycle regulator E2F-1. Forced expression of HES-1 inhibits an E 2 -mediated increase in E2F-1 and breast cancer cell proliferation (Hartman et al 2004). Estrogen response in target cells is mediated by estrogen receptors (ERs).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of osteoblast differentiation, ID4 has been shown to release Hes1 from Hes1-Hey2 complexes (44), a potentially exciting observation, because Hes1 has been shown to negatively regulate MCF7 (45) and T47D (46) proliferation stimulated by estrogen and E2F-1. In addition, these investigators have shown that the growth inhibitory effects of all-trans-retinoic acid on breast cells is mediated by Hes1 up-regulation (8), and we find that Hes1 expression is up-regulated in either CEACAM1-transfected or all-trans-retinoic acid-treated MCF7 cells (46). Thus, the sequestration of Hes1 by Hey2 may be relieved by ID4, allowing Hes1 to inhibit proliferation of MCF7 cells, a necessary step in their differentiation to lumen forming cells.…”
Section: Discussionmentioning
confidence: 49%